2023
DOI: 10.1186/s13148-023-01445-5
|View full text |Cite
|
Sign up to set email alerts
|

Distinct genome-wide DNA methylation and gene expression signatures in classical monocytes from African American patients with systemic sclerosis

Abstract: Background Systemic sclerosis (SSc) is a multisystem autoimmune disorder that has an unclear etiology and disproportionately affects women and African Americans. Despite this, African Americans are dramatically underrepresented in SSc research. Additionally, monocytes show heightened activation in SSc and in African Americans relative to European Americans. In this study, we sought to investigate DNA methylation and gene expression patterns in classical monocytes in a health disparity populatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 102 publications
0
3
0
Order By: Relevance
“…We identified only one study to analyze isolated monocytes from SSc patients [ 49 ]. The results from this study in which the authors analyzed a population of African American patients with SSc using a genome-wide DNA methylation assay demonstrated modest DNA methylation and gene expression differences between SSc patients and healthy controls.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We identified only one study to analyze isolated monocytes from SSc patients [ 49 ]. The results from this study in which the authors analyzed a population of African American patients with SSc using a genome-wide DNA methylation assay demonstrated modest DNA methylation and gene expression differences between SSc patients and healthy controls.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, this scoping review identified studies that discovered epigenetic alterations in cells of the innate immune system, including monocytes [ 22 , 49 ], DCs and pDCs [ 17 , 50 ], which highlight their role in SSc pathogenesis. Studies on PTMs in monocytes discovered altered chromatin marks that correlate with the IFN signature observed in these cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation